2005
DOI: 10.1111/j.1360-0443.2005.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the prevalence of alcohol use in rap song lyrics, 1979–97

Abstract: Many of these findings are consistent with the idea that rap music has been profoundly affected by commercial forces and the marketing of alcoholic beverages. In addition, it is possible that the increase in references to alcoholic beverages in rap music, particularly spirits, is a reflection of a broader advertising culture which increasingly associates African Americans with alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 19 publications
1
77
0
2
Order By: Relevance
“…A recent study of music popular among adolescents from 1996-1997 revealed that nearly half (47%) of all rap/hip hop (hereafter referred to as rap) songs mentioned alcohol (Roberts, Henriksen et al, 1999). In contrast, other genres of music were much less likely to mention alcohol in the lyrics (country-western (Herd, 2005). Of songs that mentioned alcohol, the positive attitude toward alcohol expressed in lyrics increased from 43% in 1970-1989 to 73% in 1994-1997.…”
mentioning
confidence: 98%
“…A recent study of music popular among adolescents from 1996-1997 revealed that nearly half (47%) of all rap/hip hop (hereafter referred to as rap) songs mentioned alcohol (Roberts, Henriksen et al, 1999). In contrast, other genres of music were much less likely to mention alcohol in the lyrics (country-western (Herd, 2005). Of songs that mentioned alcohol, the positive attitude toward alcohol expressed in lyrics increased from 43% in 1970-1989 to 73% in 1994-1997.…”
mentioning
confidence: 98%
“…Um estudo analisou, por exemplo, a prevalência da menção às bebidas alcoólicas em 341 músicas de rap no decorrer de quase duas décadas. 33 Ao observar o grande aumento nesse período às referências ao álcool, geralmente positivas, inclusive com menções a marcas específicas, o autor conclui que esse gênero musical "foi profundamente afetado por forças comerciais e pelo marketing de bebidas alcoólicas". Utilizando outro método, Zwarun 30 investigou novas maneiras pelas quais a promoção de bebidas alcoólicas têm sido feita em esportes televisivos -especialmente após questionamentos legais ocorrerem.…”
Section: Resultados 1 Estudos Descritivosunclassified
“…El hip hop y la música rap también se encuentran asociadas al uso extensivo de marihuana 61,62 , a un consumo excesivo de alcohol 63 , y más recientemente al consumo de éxtasis 64 . En un estudio reciente sobre clientes de bares en edad universitaria, Graham, Osgood, Wells y Stockwell 65 encontraron que escuchar música rap, en ese contexto social, se encuentra positiva y significativamente asociado a todos los comportamientos anteriormente mencionados -uso problemático del alcohol, consumo de drogas ilegales, y comportamientos agresivos.…”
Section: Research On Substance Use and Clubbingunclassified
“…HH and rap music have also been associated with extensive marijuana [61][62] and excessive alcohol use 63 , and more recently, ecstasy use. 64 In a recent study of collegeaged bar patrons, Graham, Osgood, Wells and Stockwell 65 found that listening to rap music in this social context was significantly and positively associated with all of the aforementioned behaviors -problematic alcohol use, illicit drug use, and aggressive behavior.…”
Section: Enfoque Metodológicomentioning
confidence: 99%